Karakterisasi Pelet Pupuk Organik Berbahan Slurry Limbah Cair Pabrik Kelapa Sawit Sebagai Pupuk Slow Release - Reni Astuti Widyowanti; Nuraeni Dwi Dharmawati; Etty Sri Hertini; Rengga Arnalis Renjani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2019)
The high availability of slurry from palm oil mill effluent, solid, and boiler ash with their nutrient contents make those three materials are potential to be processed become organic fertilizer in the form of pellet so it tends to has slow release characteristic. This research aims to analyize characteristic of organic fertilizer pellet from slurry of palm oil mill effluent as slow release fertilizer by analyzing its physical characteristics, NPK content, and NPK releasing rate in soil.Slurry was processed become solid fertilizer in the form of pellet using pellet mill with tapioca adhesive 5%. Pellet was made from slurry, solid, and boiler ash which were mixed with ratio 1:1:1, 1:2:2, 2:1:1, 2:2:1, 2:1:2, 1:0:0 (only slurry). This research ware analysis of physical characteristis (length, diameter, and density) and analysis of NPK content. N content was analyzed using Kjeldahl method, P content using spectrophotometer, and K content using Atomic Absorbtion Spectrophotometer (AAS). Then it was continued with analysis of NPK releasing content in latosol soil.The average length of pellets was 31–48 mm, diameter was 5,42 – 6,28 mm, water content was 0,426 – 0,976%, particle density was 1,04 – 1,34 g/cm3, and bulk density 0,49–0,63 g/cm3. Organic fertilizer pellet in six formulas contained N+P2O5+K2O about 5,93–8,08%. The highest content (8,08%) was produced from 1:0:0 pellet, followed by 2:1:2 formula (7,53%), and 1:2:2 formula (7,25%). Until the 10th days, the releasing of N element was about 1,99 – 3,18%, P element was 0,063– 0,075%, and K element was 43,54 – 62,26%.